BUDIDAYA IKAN DAN SAYURAN DALAM SKALA RUMAH TANGGA DI DESA GUNUNG PUTRI BOGOR - Santhuso, Agus; Waskito, Meindro; M.Affar, Sunardi Asman (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Limited land for cultivation means that the development of cultivation innovation and technology continues in line with the increasing need for food. Fish cultivation in buckets (Budikdamber) is a potential solution for fisheries cultivation and agriculture on limited land. Besides that, it can increase family food security. The advantage of the Budikdamber system is that it uses water more economically, easy for people to do at home with relatively little capital, easy to maintain, and without chemicals. The combination of catfish and water spinach in one container is the most often and easily cultivation. Optimizing the use of limited land in order to strengthen economic resilience, by strengthening household food security, households seek food from home for daily food consumption, so as to reduce household consumption expenditure without reducing the family's nutritional needs